Pembukuan Laporan Keuangan Sederhana Pada Warung Sate Cak Ummar Dan Warung Tas Rajut Pak Toe - Trirahmadi Minsyahnaz; Martinus Budiantara (Lembaga Pengembangan Kinerja Dosen, 2024)
Many MSME participants still do not understand how important it is to preserve organized financial records and bookkeeping. In actuality, business actors can determine the health of their enterprise through bookkeeping. With the help of this Community Service Activity (PKM), participants will get an awareness of the significance of business actors (MSMEs) in financial accounting and recording, as well as the procedures involved in creating financial reports. The majority of MSME participants currently maintain records, however their financial report preparation is still subpar. Training, activity implementation, and assessment are the techniques employed. The degree of comprehension exhibited by business actors both before to and during information presentation and training serves as the basis for measuring this achievement. The service's outcomes demonstrate that.